ON TRANSPORT LAYER MECHANISMS FOR REAL-TIME QoS - PAPADIMITRIOU, PANAGIOTIS; TSAOUSSIDIS, VASSILIS (Journal of Mobile Multimedia, 2005)
We study transport protocol performance from the perspective of real-time applications. More precisely, we evaluate TCP and UDP supportive role in terms of real-time QoS, network stability and fairness. A new metric for the evaluation of real-time application performance is proposed to capture both bandwidth and delay requirements. Using this metric as a primary criterion in our evaluation analysis, we reach several conclusions on the specific impact of wireless links, real-time traffic friendliness, and UDP/TCP protocol efficiency. Beyond that, we also reach an unexpected result: UDP traffic has occasionally negative impact compared with TCP traffic not only for the systemwide behavior, but also for the supporting application as well.